Sol/gel transition of oil/water microemulsions controlled by surface grafted triblock copolymer dodecyl–PEO227–dodecyl: molecular dynamics simulations with experimentally validated interaction potential. Issue 34 (11th June 2021) - Khatouri, M.; Lemaalem, M.; Ahfir, R.; El Khaoui, S.; Derouiche, A.; Filali, M.
Abstract : We studied the sol/gel transition of oil/water microemulsion (O/W-MI) covered with dodecyl–(polyEthylene oxide)227 –dodecyl triblock copolymer. Abstract : We studied a large range of identical spherical oil/water microemulsion (O/W-MI) volume fractions. The O/W-MIs are stabilized by cetylpyridinium chloride ionic surfactant (CpCl) and octanol cosurfactant and dispersed in salt water. We grafted different numbers of dodecyl–(polyEthylene oxide)227 –dodecyl triblock copolymer that we note ( n (D–PEO227 –D)), where n varies from 0 to 12. We accomplished the grafting process by replacing a small amount of CpCl and octanol with the appropriate n (D–PEO227 –D). The aim is to determine the interaction/structure relationship of the covered microemulsions. Precisely, we are interested in a quantitative investigation of the influence of volume fraction Φ, temperature ( T ), and n (D–PEO227 –D) on the microemulsion sol/gel transition. To this end, we first study the uncoated microemulsion structure depending only on Φ . Second, we determine the coated microemulsions structure as a function of n (D–PEO227 –D) for different Φ . Third, we examine the effect of temperature on the uncoated and coated microemulsion. We show that the sol/gel transition is controlled by the three main parameters, Φ, T, and n (D–PEO227 –D). Accordingly, the uncoated microemulsion sol/gel transition, at ambient temperature, occurred for Φ ≃ 33.65%. By increasing Φ, the O/W-MIs show a glass state, which occurs, along with the gel state, at Φ ≃ 37% and arises clearly at Φ ≃ 60%. The coated O/W-MI sol/gel transition is found to be linearly dependent on n (D–PEO227 –D) and takes place for Φ ≃ 26.5% for n (D–PEO227 –D) = 12. Ordinarily, the decrease in temperature leads to gel formation of microemulsions for low Φ . Additionally, in this work, we found that the gelation temperature increases linearly with n (D–PEO227 –D). Thus, the parameter n (D–PEO227 –D) can control the sol/gel transition of the O/W-MIs at ambient temperature and moderate Φ .